The Conceptual Framework and Psychometric Traits of a Survey for Testing the Functional Aspect of Negotiation Metacompetences (TMOK) - Kleka , Paweł; Kowalczyk, Elżbieta (Studia Oeconomica Posnaniensia, 2018)
The paper presents the author's questionnaire to measure the functional aspect of negotiation metacompetences based on theoretical assumptions and the results of empirical research. The items for TMOK was selected on the results obtained from a sample of 331 people (N = 217 (66%) women and N = 114 (34%) men, aged from 22 to 61 (56 for women) and mean age 31.7 (SD = 7.70) the majority of the people worked (N = 313, 94.6%) on average 9.4 years (SD = 7.35). The utility of a proposed tool for manipulation research was based on the analysis of 82 subjects (N = 47 (59.5%) women and N = 32 (40.5%) men) with a mean age of 37.4 (SD = 8.72) and average 14.6 (SD = 7.82) years of work experience), which were also examined by MACH IV and Faith in Zero- Sum Game. Low or insignificant correlations with Machiavellism and the convictions of resource constraints and satisfactory reliability parameters, as well as the results of the confirmatory analysis of the negotiation skills with TMOK justify the use of this new tool. The 16 items final version of the questionnaire TMOK for testing two dimensions: manipulation techniques (TM) and open communication (OK) is attached to the elaboration.